Bonifacy Miązek as a Historian of Poland’s Literature - Radłowska, Justyna (Transfer. Reception Studies, 2019)
The subject of this article is the presentation of the scientific achievements of Bonifacy Miązek – an emigrant poet, critic and historian of literature. This article discusses the historical/literary dissertations of a Viennese scholar published in German (Die lyrische Beschreibung im Nachkriegsschaffen Kazimierz Wierzyńskis, polnische Literatur 1863–1914. Darstellung und Analyse, Polnische Literatur des Mittelalters und der Renaissance, Studien zur polnischen Literatur). The academic books of the professor show an innovative structure which broadens the reader’s knowledge of interesting issues relating to reception aesthetics, and the reception models of Polish writers at home and abroad. Publications by Bonifacy Miązek enrich and systematize knowledge about Polish literature, expose a new look of the work of recognized authors, and introduce new names and titles.